Atmospheric Volatile Organic Compounds (VOCs) in China: a Review - Mozaffar, Ahsan; Zhang, Yan-Lin (Current pollution reports, 2020)
Purpose of Review The purpose of this review is to summarize the current understandings of atmospheric VOC characteristics in China and put forward the methodological drawbacks of the VOC measurement that need to be resolved and the research gaps that need to be filled. Recent Findings Whereas in recent investigations in the North China Plain (NCP) a reduction (20–66%) in total VOC concentration is noticed compared with the ones published before 2015, an increase (13–127%) is observed for the Yangtze River Delta (YRD) region. Aromatics and oxygenated VOCs are frequently appearing as the most abundant VOC group in recent investigations. Industry-related VOC sources are more dominant in the YRD regions while vehicle-related sources are more influential in the NCP, Central China, and Pearl River Delta regions. Benzene, 1,3,5-trimethylbenzene, ethylbenzene, naphthalene, dichloromethane, 1,2-dichloroethane, 1,2-dichloropropane, chloroform, carbon tetrachloride, and 1,2-dibromoethane pose carcinogenic risk to exposed population in China and the most risk-prone areas are affected by the petrochemical industry, biomass burning, waste management, and vehicle emissions. Formaldehyde and toluene have relatively high concentrations among the different indoor VOCs observed and their concentrations noticed to be exceeded the national air quality standard. Summary More investigations have to be performed on rarely studied health risk assessment of VOCs and characterization of indoor VOCs. BVOC studies are rarely conducted in China, which has to be performed on common plant species, different forest, and agricultural crops. VOC characterization in forest fire smokes and more process-specific emission characteristics in common industries need to be conducted.